Strategies of Legitimacy Through Social Media: The Networked Strategy - Castelló, Itziar; Etter, Michael; Årup Nielsen, Finn (Journal of Management Studies, 2016)
ABSTRACT How can corporations develop legitimacy when coping with stakeholders who have multiple, often conflicting sustainable development (SD) agendas? We address this question by conducting an in‐depth longitudinal case study of a corporation's stakeholder engagement in social media and propose the concept of a networked legitimacy strategy. With this strategy, legitimacy is gained through participation in non‐hierarchical open platforms and the co‐construction of agendas. We explore the organizational transition needed to yield this new legitimacy approach. We argue that, in this context, legitimacy gains may increase when firms are able to reduce the control over the engagements and relate non‐hierarchically with their publics. We contribute to the extant literature on political corporate social responsibility and legitimacy by providing an understanding of a new context for engagement that reconfigures cultural, network, and power relations between the firm and their stakeholders in ways that challenge previous forms of legitimation.